Efektifivas Penggunaan Media Pembelajaran SiBelur (Bebek Bertelur) Pada Hasil Belajar Siswa Dalam Pembelajaran Pengurangan Matematika Kelas 1 SDN Tlogosari Kulon 01 Kota Semarang - Febriana, Berliyan; Setyawati, Rina Dwi; Nur S, Ariani (Melati Institute, 2024)
This activity aims to evaluate how effective the use of SiBelur (Duck Laying Eggs) media is in improving Mathematics learning outcomes of grade 1 students of SDN Tlogosari Kulon 01 Semarang City. This study used a quantitative pre-experimental method with a one group pretest-posttest design. Data were collected through instruments in the form of pretest and posttest questions, which were given before and after the use of SiBelur (Duck Laying Eggs) learning media.Based on the results of research and field analysis on the use of SiBelur media as a learning tool, it can be concluded that this media shows significant effectiveness. During the activities at SDN Tlogosari Kulon 01 Semarang City, there were changes in students who previously could not do subtraction to be able to do it.